Politik Pendidikan: Studi Analitis Masa Rasulullah dan Khulafaur Rasyidin - Raikhan Raikhan (Darajat: Jurnal Pendidikan Agama Islam, 2018)
Articles were arranged in order to find out the history of education at the time of the Messenger of Allah and his Companions, in the early days of the spread of Islam on the Arabian peninsula. This study starts from socioculture and various things that support the Mental formation of a Muhammad so that he becomes a human choice, up to the approach and strategy of Muhammad in carrying out his mission as a messenger of Allah, up to the time of the Companions. This study emphasizes more on literature research by emphasizing Muhammad as a human being without seeing his personality as a messenger of Allah, by analyzing various reading sources and opinions of leaders in Islam. The full conclusion of this study states that the election of Muhammad as a brave leader, honest, fair, educator, as well as an expert in political strategy naturally has been formed from a small, It is seen from the history of life, with all the tests and challenges from the parents have left behind , herding, even trading across countries.